2020
DOI: 10.1186/s12893-020-00832-6
|View full text |Cite
|
Sign up to set email alerts
|

Urgent distal pancreatectomy for intraperitoneal hemorrhage due to the spontaneous rupture of a pancreatic metastatic tumor from synovial sarcoma: a case report

Abstract: Background: Synovial sarcoma is a soft tissue malignancy that frequently affects the extremities, adjacent to the large joints. Synovial sarcoma has a high rate of distant metastasis; however, pancreatic metastasis is extremely rare, and to our knowledge, there has been no report of bleeding due to spontaneous tumor rupture. This study reports the case of a patient with synovial sarcoma pancreatic metastasis causing tumor rupture and bleeding, which was successfully managed with emergent distal pancreatectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In a previous literature review of pancreatic metastases, most lesions were metastases of renal cell carcinoma (62.6–70.1%), followed by melanoma (4.0–9.1%), colorectal carcinoma (6.2–8.9%), and sarcoma (4.3–7.2%) [ 7 , 8 ]. Pancreatic metastasis of SS is extremely rare; only seven cases have been reported worldwide, including our case, as summarized in Table 1 [ 9 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous literature review of pancreatic metastases, most lesions were metastases of renal cell carcinoma (62.6–70.1%), followed by melanoma (4.0–9.1%), colorectal carcinoma (6.2–8.9%), and sarcoma (4.3–7.2%) [ 7 , 8 ]. Pancreatic metastasis of SS is extremely rare; only seven cases have been reported worldwide, including our case, as summarized in Table 1 [ 9 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic metastasis of SS is extremely rare; only seven cases have been reported worldwide, including our case, as summarized in Table 1 [ 9 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventional radiology is a safe and effective treatment, involving selective intra-arterial embolization and deployment of stent-grafts over the punctured vessel [ 3 ]. Only patients who develop severe complications such as abdominal hypertension syndrome and obstruction after conservative or interventional treatment require surgical treatment [ 4 , 13 ]. A 74-year-old man underwent pancreaticoduodenectomy due to the risk of malignancy and the possibility of re-bleeding [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a pancreatic tumor is an extremely rare source of spontaneous intra-abdominal bleeding. A review of the literature revealed only 10 previous case reports of spontaneous rupture of pancreatic tumors such as mucinous cyst neoplasms [12,13], pancreatic neuroendocrine cell tumors [14,15], solid cystic tumors [16,17], acinar cell carcinoma [18], pancreatoblastoma [19], and metastasis from other cancers [20,21]. To the best of our knowledge, no previous English-language report has described spontaneous intra-abdominal bleeding due to rupture of UCP.…”
Section: Discussionmentioning
confidence: 99%